The Correlation of Mother’s Knowledge about Breast Cancer and Sadari Attitude on Risk Age Moms - Mulazimah Mulazimah; Yani Ikawati; Merliana Klobe (Journal of Ners and Midwifery, 2021)
The number of cancer hospitalized patients throughout Indonesia increases year by year, as well as the increasing of mortality due to the growth of cancer patient number. In Indonesia, it is estimated that 12 out of 100,000 people face breast cancer. There are several factors that cause delays in breast cancer treatment and prevention. Eighty percent of sufferers visit a doctor or hospital at an advanced stage. The knowledge factor about breast cancer is an important thing that makes a person determines whether they do early detection or not. Early detection of breast cancer in this case is SADARI attitude. This research was done to know the correlation of mother’s knowledge levels about breast cancer and SADARI attitude at breast cancer risk age moms. This was observational research with cross sectional time approach method. The sample was 80 mothers in Badal village, Ngadiluwih Sub-District, Kediri District, East Java Province. The sampling was selected by quota sampling. Respondents with very good knowledge category who did SADARI were 26 respondents (32,5%), then respondents with good knowledge category who did SADARI were 7 respondents (8,8%), respondents who did as the instruction were 14 respondents (17,5%) and those who did not do SADARI were 8 respondents (10%), while in the less good category who did SADARI was 1 respondent (1,3%), who did not do Sadari 2 respondents (2,5%). The results of the correlation test showed that there was a significant correlation between the level of knowledge about breast cancer and SADARI attitude. With the analysis value of chi square (p=0,001 <0,005)